Fingerprint‐Inspired Conducting Hierarchical Wrinkles for Energy‐Harvesting E‐Skin. (16th August 2019) - Kang, Hyungseok; Zhao, Chunlin; Huang, Jinrong; Ho, Dong Hae; Megra, Yonas Tsegaye; Suk, Ji Won; Sun, Jia; Wang, Zhong Lin; Sun, Qijun; Cho, Jeong Ho
Abstract: In the field of bionics, sophisticated and multifunctional electronic skins with a mechanosensing function that are inspired by nature are developed. Here, an energy‐harvesting electronic skin (energy‐E‐skin), i.e., a pressure sensor with energy‐harvesting functions is demonstrated, based on fingerprint‐inspired conducting hierarchical wrinkles. The conducting hierarchical wrinkles, fabricated via 2D stretching and subsequent Ar plasma treatment, are composed of polydimethylsiloxane (PDMS) wrinkles as the primary microstructure and embedded Ag nanowires (AgNWs) as the secondary nanostructure. The structure and resistance of the conducting hierarchical wrinkles are deterministically controlled by varying the stretching direction, Ar plasma power, and treatment time. This hierarchical‐wrinkle‐based conductor successfully harvests mechanical energy via contact electrification and electrostatic induction and also realizes self‐powered pressure sensing. The energy‐E‐skin delivers an average output power of 3.5 mW with an open‐circuit voltage of 300 V and a short‐circuit current of 35 µA; this power is sufficient to drive commercial light‐emitting diodes and portable electronic devices. The hierarchical‐wrinkle‐based conductor is also utilized as a self‐powered tactile pressure sensor with a sensitivity of 1.187 mV Pa ‐1 in both contact‐separation mode and the single‐electrode mode. The proposed energy‐E‐skin has great potential for use as a next‐generation multifunctional artificial skin, self‐powered human–machine interface, wearable thin‐film power source, and so on. Abstract : An energy‐harvesting electronic skin (energy‐E‐skin), i.e., a pressure sensor with energy‐harvesting functions is developed, based on fingerprint‐inspired conducting hierarchical wrinkles. The conducting hierarchical wrinkles, fabricated via 2D stretching and subsequent Ar plasma treatment, are composed of rubber wrinkles as the primary microstructure and embedded nanowires as the secondary nanostructure.